PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN SALAM ( SYZYGIUM POLYANTHUM WIGHT) TERHADAP KADAR GLUKOSA DARAH PADA MENCIT PUTIH YANG DI INDUKSI ALOKSAN - Linta Meliala (Jurnal Penelitian Farmasi & Herbal, 2023)
Effect of Ethanol Extract of Bay Leaf (Syzygium polyanthum Wight.) Against Blood Glucose Levels In Alloxan Induced White Mice. Thesis, Department of Pharmacy, Faculty of Pharmacy, Deli Husada Deli Tua Health Institute. (Supervised by: apt. Linta Meliala, S.Si.,M.Si.) Diabetes mellitus (DM) is a metabolic disorder which is characterized by an increase in blood glucose levels. Obesity and overweight are risk factors for type 2 diabetes (WHO, 2019). One of the non-pharmacological drugs that can be used for diabetes mellitus is bay leaf. Bay leaves (Eugenia polyantha) are spread in various areas, both in the mountains and in the lowlands. To determine the antidiabetic activity of the ethanolic extract of bay leaf (Syzygium polyanthum Wight.) in alloxan-induced mice compared with glibenclamide.Experimental study using 25 mice induced with alloxan and divided into 5 groups. Group 1 (negative control) CMC Na 0.5%, group 2 (positive control) Glibenclamide dose 0.0026 mg/kgBW, group 3 bay leaf extract at 250 mg/kgBW, group 4 bay leaf extract at 500 mg/kgBW, group 5 bay leaf extract dose of 750 mg/kgBW. Extraction using maceration method with 96% ethanol as solvent. From the results of the study, each treatment group experienced a decrease in blood glucose levels. Of the 5 treatment groups, the best reduction in blood glucose levels was glibenclamide. The positive control of glibenclamide produced a faster reduction effect than the ethanolic extract of bay leaf. The greatest effectiveness in the ethanol extract of bay leaf 750 mg/kgBW with a faster decrease in blood glucose levels was almost equivalent to the positive control. Ethanol extract of bay leaf (Syzygium polyanthum) can reduce blood glucose levels in male white mice induced with alloxan